2021
DOI: 10.1021/acsaem.0c02120
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Desired Fabrication Factors from Modeling Sandwich and Quasi-Interdigitated Back-Contact Perovskite Solar Cells

Abstract: A numerical simulation method is used to investigate the optical and electrical properties of both conventional sandwich and quasi-interdigitated back-contact (QIBC) perovskite solar cells (PSCs). The results reveal the fundamental physics of PSCs with different architectures, exhibiting their difference in working principle and device properties. A two-dimensional optical model, which takes into account both the electromagnetic and electronic properties of various device layers, is selected to accurately desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Perovskite solar cells (PSCs) have emerged as a breakthrough photovoltaic (PV) technology, holding unprecedented promise for high-efficiency, low-cost solar cells due to their excellent photoelectric properties. However, the potential toxicity associated with the lead-containing PSCs has become a major concern. The primary drawback of Pb perovskites for solar cells is that soluble Pb compounds are well known to be toxic to both the natural environment and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have emerged as a breakthrough photovoltaic (PV) technology, holding unprecedented promise for high-efficiency, low-cost solar cells due to their excellent photoelectric properties. However, the potential toxicity associated with the lead-containing PSCs has become a major concern. The primary drawback of Pb perovskites for solar cells is that soluble Pb compounds are well known to be toxic to both the natural environment and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ETL and HTL are positioned side-by-side at the same side, inhomogeneous electric field distribution is formed inside the perovskite absorber layer with a lateral field direction. , Therefore, the performance of the back-contact architecture is known to be easily influenced by the geometric parameters (e.g., the width of the Q-IDE area) of the device. Specifically, it has been demonstrated that the J SC and FF are affected by the width of the Q-IDE area, ,, which is referred to as the Q-IDIE in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement of transmittance was confirmed with transparent ITO/NiO X electrodes compared to the Ni/NiO X shell, presented in Figure S11. With transparent electrodes, the device performance is expected to improve while the amount of incident light reaching the bottom cell increases. Since the ETL and HTL are positioned side-by-side at the same side, inhomogeneous electric field distribution is formed inside the perovskite absorber layer with a lateral field direction. , Therefore, the performance of the back-contact architecture is known to be easily influenced by the geometric parameters (e.g., the width of the Q-IDE area) of the device. Specifically, it has been demonstrated that the J SC and FF are affected by the width of the Q-IDE area, ,, which is referred to as the Q-IDIE in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Our cooling scheme can be integrated with various competing configurations of thin-film solar cells, like various types of backcontact geometries, to further enhance the light-harvesting power, also allowing the perovskite layer to be deposited at a later stage, preventing its degradation during the fabrication process. 24 To derive optimal design parameters and spectral properties, we employ a simple, analytical generic opto-electrothermal model adopted for polymer-and for perovskite-based cells. 22 The model considers all crucial macroscopic (i.e., sunlight absorption, emission, nonradiative heat exchange) and microscopic processes (i.e., carrier generation, recombination, and collection, as well as thermalization of hot generated carriers) of the cooler−cell system, in a broad wavelength range (e.g., 0.28−33 μm), i.e., considering both the thermal wavelengths (≥4 μm), including the atmospheric transparency window (8−13 μm), and the solar wavelengths (0.28−4 μm).…”
Section: ■ Introductionmentioning
confidence: 99%